PENGARUH AUDIT KINERJA DAN PENYAJIAN LAPORAN KEUANGAN TERHADAP AKUNTABILITAS PUBLIK PADA ORGANISASI PERANGKAT DAERAH KOTA PEKANBARU - Utari Praweswari; Muhammad Ahyaruddin; Wira Ramashar (Jurnal Akuntansi Kompetif, 2024)
In this study, the researcher found that the variables Performance Audit and Presentation of Financial Reports together had a significant influence on Public Accountability in Pekanbaru City Regional Apparatus. For the F test, you can see Fcount= 13.627 > Ftable= 3.191. The significant value in the F test is 0.000. Because Sig 0.000 < 0.05, then as the basis for decision making in the F test it can be concluded that Performance Audit (X1), Presentation of Financial Reports (X2), simultaneously together influence the Public Accountability of Pekanbaru City Regional Apparatus (Y) or means significant. The coefficient of determination shows a value of 0.377. This shows that 37.7% of performance is influenced by the determining variables in the model such as Performance Audit and Presentation of Financial Reports, while the remainder (62.3%) is explained by other variables not included in this research. Thus, it can be seen that there are many other factors that influence public accountability apart from performance audits and presentation of financial reports.